Prevalence of Restless Legs Syndrome in Patients with Type 2 Diabetes and Its Impact on Daytime Sleepiness: Restless Legs Syndrome in Patients with Type 2 Diabetes - Mehmood, Nasir; Iqbal, Maryam; Raheem, Rameez; Chandran, Suryiakala Perumal; Ahmed, Waqas (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
The sleep-related sensorimotor disorder is known as restless legs syndrome (RLS) and may impair the continuity of sleep and lead to impairment of daytime functioning. Objectives: To measure the prevalence of restless legs syndrome among adult patients with type 2 Diabetes Mellites and to explore the relationship that exists between restless leg syndrome and daytime sleepiness. Methods: A non-probability convenience sample was used to recruit 400 adults (40-59 years) with T2DM and HbA1c level exceeding 6.5 percent in both hospitals, which are called the participants of the study (District Headquarter Hospital, Lodhran, and Bahawal Victoria Hospital, Bahawalpur). The RSL-Diagnostic Index (RLS-DI) was used to screen RLS, and the Epworth Sleepiness Scale (ESS) was used to classify daytime sleepiness. The Pearson chi-square test was used to test the association between RLS and daytime sleepiness; Cramer's V was used to summarize the effect size. The presence of excessive daytime sleepiness (ESS > 10) was also estimated by an unadjusted logistic regression (2×2) using exploratory estimation. Results: 72 had positive results for RLS, and the prevalence was 18.0 (95% CI 13.323.9). ESS categories were: normal 39.0%, mild sleepiness 25.5%, moderate sleepiness 8.5%, and severe sleepiness 27.0%. Distribution of ESS categories did not differ significantly by RLS status (χ²=0.976, p=0.807; Cramer’s V=0.070). Exploratory analysis dichotomizing ESS suggested no increased odds of excessive daytime sleepiness among participants with RLS. Conclusions: Restless leg syndrome was relatively common among adults with type 2 Diabetes Mellitus in this region, but RLS status was not significantly associated with ESS-derived daytime sleepiness.